2009
DOI: 10.4315/0362-028x-72.10.2071
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Salmonella enterica in Laying-Hen Flocks and Assessment of Eggshell Contamination in France

Abstract: The present investigation was conducted in conjunction with the European Union baseline study for the estimation of Salmonella prevalence in laying-hen flocks. It aimed at evaluating eggshell contamination in farms positive for Salmonella, characterizing the genetic patterns of Salmonella strains and identifying the factors associated with Salmonella contamination of eggshells. For this purpose, a total of 4,200 eggs were collected from 28 positive flocks and analyzed according to draft Annex D of Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 22 publications
4
26
2
3
Order By: Relevance
“…Field studies have found a correlation between the number of positive environmental samples and the proportion of eggs positive in a flock (Kinde et al, 1996;Davies and Breslin, 2004;Chemaly et al, 2009;Renu and Tripathi, 2011), suggesting that prevalence of infection and on-farm hygiene are directly related to the number of contaminated eggs produced (Arnold et al, 2014b). Eggshell contamination occurs more frequently than the contamination of the egg contents Davies and Breslin, 2004;Little et al, 2007b;Little et al, 2008).…”
Section: Salmonella Prevalence and Serovar Distribution Among Isolatementioning
confidence: 99%
See 2 more Smart Citations
“…Field studies have found a correlation between the number of positive environmental samples and the proportion of eggs positive in a flock (Kinde et al, 1996;Davies and Breslin, 2004;Chemaly et al, 2009;Renu and Tripathi, 2011), suggesting that prevalence of infection and on-farm hygiene are directly related to the number of contaminated eggs produced (Arnold et al, 2014b). Eggshell contamination occurs more frequently than the contamination of the egg contents Davies and Breslin, 2004;Little et al, 2007b;Little et al, 2008).…”
Section: Salmonella Prevalence and Serovar Distribution Among Isolatementioning
confidence: 99%
“…S. Senftenberg, S. Livingstone, S. Infantis) are occasionally isolated from eggs, mainly from eggshells, but also rarely from egg contents (Martelli and Davies, 2012). S. Infantis has been isolated from eggs in several surveys carried out in Europe ((de Louvois, 1993;Little et al, 2007a;Murchie et al, 2007;Wilson, 2007;Chemaly et al, 2009;Martelli and Davies, 2012). S. Infantis is also associated with egg and human illness in geographical areas outside Europe, such as Japan and New Zealand (Lapuz et al, 2008;Wilson, 2007).…”
Section: Salmonella Prevalence and Serovar Distribution Among Isolatementioning
confidence: 99%
See 1 more Smart Citation
“…Other serovars i.e. S. Mbandaka, S. Heidelberg, S. Hadar, S. Infantis and S. Virchow, could also occur with low frequency in layers and consequently on egg surfaces (Chemaly et al, 2009). Their occurrence varies greatly between continents and countries (Poppe, 1992;Snow et al, 2007;EFSA, 2007).…”
Section: Patho-biology Of Different Salmonella Serovars In Laying Hensmentioning
confidence: 99%
“…In Austria, the factor associated with Salmonella status was cage housing (Much et al, 2007). In France, RFs associated with Salmonella contamination of eggshells were; entry of delivery trucks near the poultry house entrance, flock size, more than five culture positive environmental samples, high egg-laying rate and mixed farming (Chemaly et al, 2009). …”
Section: Dynamics Of Salmonella Infection In the Laying Hen Flockmentioning
confidence: 99%